Solve 2*l - 6*d + 11*d - 4 = 0, -5*d = -11*l + 87 for l.

7

Solve 8 = 4*o, -6 = -2*a + 7*a - 3*o for a.

0

Solve -18*z = 2*s - 22*z + 8, 0 = 5*s + 4*z + 20 for s.

-4

Solve r - 5*t + 5 = 0, 4 = -5*r - 0*r + 4*t for r.

0

Solve -1 = 2*t + 4*s - 5*s, 4*t - s = -7 for t.

-3

Solve 3*o + 3*x - 5*x = 7, 2*o = -x for o.

1

Solve 0 = -4*h + 16, 3*b - 2*h = 2 + 5 for b.

5

Solve 2*x - 11 = -0*x - 3*w, -w = -1 for x.

4

Solve 10*k + 3*y + 9 = 7*k, -3*k - 8 = 4*y for k.

-4

Solve -25*i - 16 = 2*h - 23*i, -2*h = -i + 7 for h.

-5